DAMPAK PENERAPAN DIGITALISASI ARSIP DI DESA CIBOGO KEC.CIBOGO, KAB.SUBANG TERHADAP KEGIATAN PELAYANAN MASYARAKAT - Saepudin, Asep; Rusilpan, Ilpan; Jupriyanto; Carkiman (Jurnal Teknologi Informasi dan Komunikasi, 2024)
The ever-increasing development of digitalization has made village governments begin to apply it in the process of providing services to the community and in the process helps facilitate the work carried out by employees, thereby making the service process fast and easy. Digital archives are used to simplify the process of searching for archives that have been created and reduce physical archives that require space for storage. By using observation and interview research methods as well as system development methods using waterfall, the results obtained from this research are that the digital archive system can run well and can be used by users. If a digital archive system is compared with conventional archives, the result is that digital archives can improve service quality, making it easier for employees to manage archives. Digital archives can reduce paper use by 50 percent, thereby reducing environmental impacts caused by paper use, such as cutting down trees and pollution from the use of chemicals